Prevalence of hyponatraemia in patients over the age of 65 who have an in-hospital fall - Carmen Lobo-Rodríguez; Ana M. García-Pozo; Carmen Gadea-Cedenilla; M. Nieves Moro-Tejedor; Azucena Pedraz Marcos; Alberto Tejedor-Jorge (Nefrología (English Edition), 2016)
Background and aim: Hyponatraemia is the most common electrolyte disorder. Some studies have found that it increases morbidity and mortality. There are new lines of research that are investigating the link between hyponatraemia and patient falls. Aim: To determine if hyponatraemia is associated with falls in elderly hospitalised patients. Methods: Design observational, analytical, case–control study. Study population: Patients older than 65 years who had fallen during their hospitalisation at Gregorio Marañón Hospital (Madrid) were considered cases. Patients who did not fall were considered to be controls, paired according to the following variables: hospital ward, age, length of hospital stay, gender and Downton fall risk index. The sample size was 206 subjects. Data collection: Socio-demographic factors, variables included in the falls record sheet, Downton fall risk index and sodium levels were studied (hyponatraemia was considered Na+ < 135 mmol/l). Analysis: A descriptive analysis was performed to determine the sample homogeneity. The OR was calculated, and an analytical analysis using Chi-square test and a multivariate logistic regression analysis were also performed. Results: Of 103 cases recruited, 61 were men (50.4%) and 42 were women (49.4%). Hyponatraemia was detected in 29 cases with an association with falls of P: 0.002. The adjusted OR was 3.708 (1.6–8.3), 95% CI. Risk factors for falls were identified as hyponatraemia and limb sensory deficits. Conclusions: Given that hyponatraemia could be considered a risk factor for falls, the inclusion of the determination of sodium level would be important for fall prevention strategies in the elderly.